2018
DOI: 10.1016/j.electacta.2017.11.072
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of a cell for the electrochemical synergistic production of peroxoacetic acid

Abstract: Highlights Peroxoacetic acid (PAA) is efficiently produced electrochemically from acetic acid  The production of hydrogen peroxide is crucial for an efficient accumulation of PAA  BDD is superior to DSA as anode material for PAA production  High current densities hinder the accumulation of PAA and hydrogen peroxide  Flow from anode to cathode improves the process of PAA production

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…The first one is the flow pattern of both reactors. In our previous work, it was demonstrated that when the fluid passed first through the anode chamber and then through the cathodic side of the reactor (flow anode–cathode), the rate of PAA production was higher than with a cathode–anode configuration. In the case of the jet reactor presented in this work, it is difficult to work with an anode–cathode configuration because the inlet of the reactor in the anode side is perpendicular and a high tangential velocity is required to assure an adequate flow of air through the jet device.…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…The first one is the flow pattern of both reactors. In our previous work, it was demonstrated that when the fluid passed first through the anode chamber and then through the cathodic side of the reactor (flow anode–cathode), the rate of PAA production was higher than with a cathode–anode configuration. In the case of the jet reactor presented in this work, it is difficult to work with an anode–cathode configuration because the inlet of the reactor in the anode side is perpendicular and a high tangential velocity is required to assure an adequate flow of air through the jet device.…”
Section: Resultsmentioning
confidence: 97%
“…First, we presented a prototype in which we performed the production of PAA from CH 3 COOH aqueous solutions combining the oxidation of CH 3 COOH by boron-doped diamond (BDD) anodes and the cathodic production of H 2 O 2 using a carbon-based gas diffusion electrode (GDE). 13,14 With this design, we observed a clear synergistic effect when combining both the anodic and the cathodic processes in the production of PAA, resulting in the highest concentration reported so far in the literature for the electrochemical production of PAA. Moreover, in those works, we demonstrated that the flow direction (from cathode to anode or vice versa) played an important role in the efficiency of the process.…”
Section: Introductionmentioning
confidence: 80%
See 3 more Smart Citations